IMPACT OF BODY MASS INDEX (BMI) AND DURATION OF PHASE I CARDIAC REHABILITATION AFTER CORONARY ARTERY BYPSS GRAFT (CABG). - AJITH S,; IVOR PETER D’SA,; M GOPALA KRISHNAN, (International Journal of Pharma and Bio Sciences, 2014)
Extremely thin and overly obese patients may not tolerate cardiac surgery as well as other patients. The exact relationship between BMI and duration of Phase I cardiac rehabilitation has not yet been defined. Our objective was to assess the influence of BMI on duration of Phase I cardiac rehabilitation after Coronary Artery Bypass Graft (CABG). Patients posted for CABG were divided in to 4 groups based on the BMI. After the surgery Phase I cardiac rehabilitation was administered. Arterial blood gas values and duration of hospital stay were collected from all four groups and analyzed. Pulmonary complications were more in underweight group when compared to the other groups and the normal weight group spend the least number of days in hospital when compared with the other groups (P=.000).The duration of Phase I cardiac rehabilitation will vary with the BMI of the patients.